Perioperative outcomes of robotic lobectomy for early-stage non-small cell lung cancer in elderly patients - Gallina, Filippo Tommaso; Tajè, Riccardo; Forcella, Daniele; Gennari, Valeria; Visca, Paolo; Pierconti, Federico; Coccia, Cecilia; Cappuzzo, Federico; Sperduti, Isabella; Facciolo, Francesco; Melis, Enrico (Frontiers in Oncology, 2022)
Introduction Minimally invasive surgery has become the standard of the early stage NSCLC. The appropriateness of the kind of lung resection for the elderly patients is still debated. Methods We retrospectively reviewed patients with > of 75 years who underwent robotic lobectomy between May 2016 to June 2022. We selected 103 patients that met the inclusion criteria of the study. The preoperative cardiorespiratory functional evaluations were collected and the risk of postoperative complications was calculated according to the Charlson Comorbidity Index, the American College of Surgery surgical risk calculator (ACS-NSQIP), EVAD score, American Society of Anaesthesiology score (ASA). The patients were divided in two groups according to the presence of postoperative complications. Results 43 patients were female and the 72.8% of the total population were former or active smoker. 35 patients reported a postoperative complications. The analysis of the two groups showed that the predicted postoperative FEV1 and FVC were significantly lower in patients presenting post-operative complications (p=0.04). Moreover the upstaging rate and the unexpected nodal metastases were more higher in the postoperative complications groups. Conclusion Robotic assisted lobectomy for early-stage lung cancer is a safe and feasible approach in selected elderly patients. The factors that could predict the complication rate was the predicted postoperative FEV1 and the nodal disease.